Economic analysis of paliperidone long-acting injectable for chronic schizophrenia in Portugal. (1st September 2016) - Einarson, Thomas R.; Maia-Lopes, Susana; Goswami, Pushpendra; Bereza, Basil G.; Van Impe, Kristel
Abstract: Objective: Patients with chronic schizophrenia suffer a huge burden, as do their families/caregivers. Treating schizophrenia is costly for health systems. The European Medicines Agency has approved paliperidone palmitate (PP-LAI; Xeplion), an atypical antipsychotic depot; however, its pharmacoeconomic profile in Portugal is unknown. A cost-effectiveness analysis was conducted from the viewpoint of the Portuguese National Health Service. Methods: PP-LAI was compared with long acting injectables risperidone (RIS-LAI) and haloperidol (HAL-LAI) and oral drugs (olanzapine; oral-OLZ) adapting a 1-year decision tree to Portugal, guided by local experts. Clinical information and costs were obtained from literature sources and published lists. Outcomes included relapses (both requiring and not requiring hospitalization) and quality-adjusted life-years (QALYs). Costs were expressed in 2014 euros. Economic outcomes were incremental cost-effectiveness ratios (ICERs); including cost-utility (outcome = QALYs) and cost-effectiveness analyses (outcomes = relapse/hospitalization/emergency room (ER) visit avoided). Results: The base-case cost of oral-OLZ was 4447€ (20% drugs/20% medical/60% hospital); HAL-LAI cost 4474€ (13% drugs/13% medical/74% hospital); PP-LAI cost 5326€ (49% drugs/12% medical/39% hospital); RIS-LAI cost 6223€ (44% drugs/12% medical/44% hospital). Respective QALYs/hospitalizations/ER visits were oral-OLZ: 0.761/0.615/0.242; HAL-LAI: 0.758/0.623/0.250; PP-LAI: 0.823/0.288/0.122; RIS-LAI: 0.799/0.394/0.168. HAL-LAI was dominated by oral-OLZ and RIS-LAI by PP-LAI for all outcomes. The ICER of PP-LAI over oral-OLZ was 14, 247€/QALY, well below NICE/Portuguese thresholds (≈24, 800€/30, 000€/QALY). ICERs were 1973€/relapse avoided and 2697€/hospitalization avoided. Analyses were robust against most variations in input values, as PP-LAI was cost-effective over oral-OLZ in >99% of 10, 000 simulations. Conclusion: In Portugal, PP-LAI dominated HAL-LAI and RIS-LAI and was cost-effective over oral-OLZ with respect to QALYs gained, relapses avoided, and hospitalizations avoided.